2009
DOI: 10.1007/s00264-009-0738-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical environment on the evolution of Kashin-Beck disease in Tibet

Abstract: In previous studies we observed a proximo-distal gradient of lesion frequencies along the limb, with the distal joints being the most often affected. This suggests an associated effect of environmental factors on the most exposed joints. On a population of 820 children (mean age 13 years) of endemic areas distributed in groups of healthy and severity stages I to III of KBD (Kashin-Beck disease), the effects of different working activities were studied. Heavy work like that of a ploughman were compared to light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…In seriously affected patients, this disease leads to shortened stature or dwarfism and disability in their daily life [2]. The physical environment will aggravate the evolution of the disease accelerating the OA lesions [12]. For some severely affected patients surgery will be needed to reconstruct the affected joints [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…In seriously affected patients, this disease leads to shortened stature or dwarfism and disability in their daily life [2]. The physical environment will aggravate the evolution of the disease accelerating the OA lesions [12]. For some severely affected patients surgery will be needed to reconstruct the affected joints [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…During the early stage of KBD, environmental risk factors (for example mycotoxins) damage the epiphyseal plate cartilage, epiphyseal cartilage, and articular cartilage, leading to extensive necrosis and apoptosis of chondrocytes and disturbance of endochondral ossification (17)(18)(19). With increasing age, KBD patients manifest joint deformities, which result in local overload of joints and accelerate the degeneration of articular cartilage (17,20,21). It has been demonstrated that osteotomy to correct the mechanical unbalance of joints is capable of improving the joint functions of adult KBD patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies showed that the risk factors for KBD included low socio-economic status, trace element deficiency, fungal contamination, low dietary antioxidants, protein-calorie malnutrition, physical environment (microtrauma and cold) and other factors [18,19]. However, no single factor could explain the pathogenesis of KBD.…”
Section: Discussionmentioning
confidence: 99%
“…However, no single factor could explain the pathogenesis of KBD. Multifactorial aetiology should be considered in the study of KBD [18]. Although it is not known whether animals living in KBD endemic regions suffer from this disease, many authors have tried to reveal the mechanism of KBD through animal experiments.…”
Section: Discussionmentioning
confidence: 99%